Mapping the amide I absorption in single bacteria and mammalian cells with resonant infrared nanospectroscopy. (18th January 2016) - Baldassarre, L; Giliberti, V; Rosa, A; Ortolani, M; Bonamore, A; Baiocco, P; Kjoller, K; Calvani, P; Nucara, A
Abstract: Infrared (IR) nanospectroscopy performed in conjunction with atomic force microscopy (AFM) is a novel, label-free spectroscopic technique that meets the increasing request for nano-imaging tools with chemical specificity in the field of life sciences. In the novel resonant version of AFM-IR, a mid-IR wavelength-tunable quantum cascade laser illuminates the sample below an AFM tip working in contact mode, and the repetition rate of the mid-IR pulses matches the cantilever mechanical resonance frequency. The AFM-IR signal is the amplitude of the cantilever oscillations driven by the thermal expansion of the sample after absorption of mid-IR radiation. Using purposely nanofabricated polymer samples, here we demonstrate that the AFM-IR signal increases linearly with the sample thickness t for 50 nm, as expected from the thermal expansion model of the sample volume below the AFM tip. We then show the capability of the apparatus to derive information on the protein distribution in single cells through mapping of the AFM-IR signal related to the amide-I mid-IR absorption band at 1660 cm −1 . In Escherichia Coli bacteria we see how the topography changes, observed when the cell hosts a protein over-expression plasmid, are correlated with the amide I signal intensity. In human HeLa cells we obtain evidence that the protein distribution in the cytoplasm and in the nucleus is uneven, with a lateral resolution better than 100 nm.